Argentina - Women Weaving Equitable Gender Relations - Stubbs, Josefina (World Bank, Washington, DC, 2012)
In 2001, after a long period of recession, Argentina faced the greatest economic, political, and institutional crisis in its history. Unemployment reached levels nearing 18 percent and the poverty rate reached a peak of 58 percent in 2002, increasing twofold the number of people living the poverty line and impacting in a disproportionate manner the most vulnerable and poverty stricken families. The crisis also had a tremendous impact on Argentina's middle-class. Increased unemployment and the freezing of wages and bank deposits forced many families to face poverty for the first time, and to seek new survival strategies. The crisis caused the rupture of traditional roles within the household, forcing many women into the workforce, many young people to leave school in search of a job, and many traditional breadwinners to remain at home. In many cases, these changes challenged not just the economic viability of households but the role of families. Recognizing the potential impact of the situation, the Government of Argentina approached the World Bank for a small loan ($5 million), aimed at promoting gender equity and the development of families through the Family Strengthening and Social Capital Promotion Project (PROFAM). The main objective of PROFAM was to address the vulnerability of the poorest and weakest segments of the population by targeting families as a comprehensive unit, and by strengthening the development of each member, from a gender perspective. PROFAM actively promoted coordinated and cohesive cooperation between civil society organizations, local governments and the families themselves, and strengthened local capabilities to design, manage and implement projects through associative networks. PROFAM also encouraged the joint development of alternative poverty-reduction strategies, focusing on extremely vulnerable families.